Plan de Marketing aplicado en la empresa Rey Metal, de la Ciudad de Loja - Yanza Saquisares, Yuri Deyne (2017)
The present research work has as general objective, to design a Marketing Plan for the company Rey Metal, in the city of Loja. Considering it as an accepted tool, that allows to establish the activities of the organization, and the decision making to achieve a better positioning in the market of the company object of study. For the achievement of objectives, it was necessary to use a methodology, the use of the inductive method, which allowed the internal analysis to identify the strengths and weaknesses of the organization, and the deductive method was used for the purpose of analyzing the external analysis And competitive to identify opportunities and threats, the techniques used were: observation, interview and surveys, which made it possible to collect the necessary information about the behavior of clients and thus finalize the current diagnosis of the King Metal company. In the results it was established that the company Rey Metal, has opportunities such as: environmental legislation has incorporated great advances in terms of environmental and recycling policies; The increase of the population growth rate, is a determining factor of the increasing behavior of the recycling sector; Promotion of recycling activity at national level and technological and information technology innovation; It also has threats such as: high public spending and rising taxes, accompanied by lower inflows of foreign currency into the country due to the drop in the price of a barrel of oil and the strengthening of the dollar against the currencies of Neighboring countries, causes uncertainty in the recycling 6 sector; Existence of several recycling; High bargaining power of customers in the products offered by the company; Unfair competition from other recycling establishments. In the competitive analysis it was determined that the company has a market positioning with a weighted total of 2.62, being able to identify thanks to the factors of success as: Competitiveness of the price, Quality of customer service, market share, turnover , Distribution channels and strategic location; Its direct competitors are: the company REYPAP, and the company Narváez. In the internal analysis the strengths were determined as: location, the company has its own premises; Offers its customers competitive prices; They have stable and experienced staff; The services provided to the clients both in knowledge of the product offered and in care are very good; Likewise, weaknesses such as: do not have a Marketing Plan; Do not provide training to staff; Lack of promotion and publicity in recognized media; There is no statement of mission and vision. With the help of the SWOT matrix, we identified the strategies and strategic objectives of the Marketing Plan, which the company must apply with the purpose of positioning itself in the recycling sector. For the development of the present Marketing Plan, essential and pertinent parameters were defined which consist of objectives, goals, tactics, policies, budget and financing, for each of the proposed strategic objectives. 7 Finally, conclusions and recommendations were drawn up based on an analysis carried out at the company REY METAL, hoping that they will be taken into account and implemented by the manager of the recycler Rey Metal, in order to improve its development and provide greater utility.